THE DEVELOPMENT OF THEORETICAL FRAMEWORK FOR THE BEHAVIORAL MANAGEMENT OF USED DRY BATTERIES IN A HOUSEHOLD - Pruekparichart, Montee; Techato, Kuaanan; Isaramalai, Saengarun; Sangkakool, Tachaya (PEOPLE: International Journal of Social Sciences, 2017)
Nowadays, most households use dry batteries even though they are hazardous waste at the end of the lifetime. Actually, the waste must be separated, collected and disposed. However, this basic household hazardous waste management has not been successfully managed in Thai households. So the objective of this research was to develop the household behavior in using dry batteries prediction model. The methodology was divided into 3 steps. The first step is to define the concept and the operational definition of variables. The second step including the preliminary steps shows the questionnaire content. The third step is the score indicators in questionnaire. This research results are; 1) content validity test 2) reliability test and 3) the prediction model. It can be indicated into 3 major components. The first component consists of household factors, which are perception, social influence, optional vision, and knowledge. The second component relates to environmental factors, which are receiving information, experience, and reinforcement. The third component is intention. This modeling will be formed into structural equation model including interpret for the policy maker and planner. It will be able to manage the used batteries from household in accordance with the conditions of each local municipality more effectively.